Pengaruh Tricuspid Annular Plane Systolic Excursion (TAPSE) Pasca Pembedahan Katup Mitral Terhadap Mortalitas Jangka Panjang - Erriyanti, Sabrina; Soesanto, Amiliana M; Sakidjan, Indriwanto; Atmosudigdo, A.; Lilyasari, Oktavia; Ariani, Rina; Siagian, Sisca Natalia (Jurnal Kardiologi Indonesia, 2022)
Background: Heart valve disease is still a significant health burden in the world, including Indonesia. The postoperative outcome of mitral valve surgery is influenced by many things, including decreased right ventricular (RV) function, which is the most common complication. Several studies have shown that decreased RV function after mitral valve surgery is associated with long-term outcomes. TAPSE is a routine and easy measurement of RV systolic function. A decrease in TAPSE after cardiac surgery is common because of the effects of pericardiotomy, and does not necessarily reflect a decrease in RV ejection fraction (RVEF). Regardless of whether postoperative TAPSE values ​​indicate right ventricular systolic function or only due to the effects of pericardiotomy, it is still not clear whether postoperative TAPSE values ​​have a prognostic value to long-term mortality after mitral valve surgery. Therefore, the objective of this study is to obtain information regarding the relationship of TAPSE echocardiographic parameters after mitral valve surgery with long-term mortality. Methods: This is a retrospective cohort study, looking at the effect of TAPSE on outcome after mitral valve surgery. The analysis starts from the starting point of the study when the patient was discharged alive from the hospital after mitral valve surgery (operation period January 2016 – February 2017) to the end point of the study, which was June 30th, 2021 and the observed outcome was mortality from any cause. Results: Of the 266 study subjects, 11 subjects died within 4-5 years after mitral valve surgery, the mortality is 4%. Bivariate analysis was performed on several factors and no relationship was found between the analyzed variables and mortality. Conclusion: There is no relationship between mortality and TAPSE after mitral valve surgery. This article has a related Erratum.